The factors towards to use behavior among private employers using E Goverment application: JOBSMALAYSIA system / Nor Azila Awang Abu Bakar, Nur Mimi Adila Ismail and Nazatul Azleen Zainal Abidin - Mohamad Yusof, Yau’mee Hayati; Md Sabri, Sabiroh; Abdul Aziz, Nurul Ulfa (2015)
In order to achieve the objective of this research, two research questions have been constructed. The research questions were constructed on theoretical considerations found in the literature review. Since the aim of this research is to explore the behaviour of the JOBSMALAYSIA system, the study is descriptive in its nature. The study primarily uses the Technology Acceptance Model (TAM) and The Unified Theory of Acceptance and Use of Technology (UTAUT) Model as the theoretical basis. Both theories are widely used in information technology and information systems research to evaluate user acceptance of a system and to understand determinants of individual behaviour towards the system usage. The Ordinal and nominal scale were applied to thirty-two items. Out of 188 distributed questionnaire which used convenient sampling, only 57 usable responses were returned by the respondents among the private employers in Terengganu Darul Iman. The questionnaires were distributed by using postal, hand to hand delivery, faxes and also email. Although the return rate of the survey is only 30.3 %, but it has proved by prior research sample that use TAM or other user acceptance model shows that their response rates were also below 20%, similar to our case. This paper will discuss the factors towards to use behavior among private employers in the East Coast of Malaysia towards E-Government application: JOBSMALAYSIA system. It was found that the anxiety factor was chosen to be the most agreed factors among others. This study should also be able to highlight and emphasize the importance of user involvement during the development of a new system especially as the reference for the Government in the future.